Legal Protection for Famous Brands on Dissimilar Products - Dian Utari (Journal of Innovative and Creativity, 2026)
The protection of famous brands is regulated within the Paris Convention and the TRIPs Agreement. Famous brand is one that holds a high reputation in the trading world. Legal protection for famous brands on dissimilar products is governed by Article 16 of the TRIPs Agreement, which mandates countries that have ratified TRIPs to also regulate the legal protection of famous brands, even extending it to dissimilar products. Indonesia, as one of the countries that ratified it, is obligated to provide legal protection guarantees for famous brands on dissimilar products. This article aims to examine the implementation of extending the protection of famous brands to dissimilar products within Indonesia's legislative regulations and the factors causing this extension to apply to dissimilar products. Research findings indicate that Indonesia began regulating the protection of famous brands on dissimilar products under Law Number 14 of 1997 concerning Trademarks and currently under Law Number 20 of 2016 concerning Trademarks and Geographical Indications. The factors causing the extension of protection for famous brands to dissimilar products include safeguarding brand reputation, protecting ownership rights over the brand, preventing trademark infringements, interests of license holders, economic interests, fostering innovation and investment, as well as serving as a form of consumer protection.